Political Selection and the Concentration of Political Power - Andreas Grunewald; Emanuel Hansen; Gert Pönitzsch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper studies the effects of power-concentrating institutions on the quality of political selection, i.e., the voters' capacity to identify and empower competent politicians. In our model, candidates are privately informed about their abilities and are driven by office rents as well as welfare considerations. We show that variations in power concentration involve a trade-off. On the one hand, higher concentration of power enables the voters' preferred politician to enforce larger parts of his agenda. On the other hand, higher power concentration increases electoral stakes and thereby induces stronger policy distortions. We identify a negative relation between the optimal level of power concentration and the extent of office motivation. In particular, full concentration of power is desirable if and only if politicians are mostly welfare-oriented. The results of an empirical analysis are in line with this prediction.
Keywords: D72; D82; H11; 330